Heat-inducible autolytic vector for high-throughput screening. (September 2006) - Xu, Lihua; Li, Shuang; Ren, Chuan; Cai, Zhen; Lin, Zhanglin
In directed evolution, a high-throughput screening system is often a prerequisite for sampling the enzyme variants. When the target enzyme is expressed intracellularly, for example when Escherichia coli is used as the host, chemical or enzymatic disruption of cell membrane is often required in many cases, which can be tedious, time-consuming, and costly. In this study, a set of heat-inducible autolytic vectors were constructed to solve this problem, in which the SRRz lysis gene cassette from bacteriophage λ was placed downstream of heat-inducible promoters, λ cI857/pR promoter and its mutant, cI857/pR (M). The artificial autolytic units were inserted into the backbone of pUC18 (away from the multiple cloning sites). For the wild promoter, cI857/pR, the SRRz lysis cassette was expressed by temperature up-shift from 28° to 38°C, and the lysis efficiency of transformed bacterial cells was found to be consistent and could reach 96.3% as measured by the reporter β-galactosidase assay. In order to obtain a higher cell growth rate, the mutant promoter cI857/pR (M) was utilized to allow bacteria growth at 35°C and lysis at 42°C. However, this heat-inducible system showed significant inconsistency in terms of lysis efficiency. Bacillus subtilis 168 lipase A gene was further in-serted into the multiple cloning sites of the autolytic vector containing cI857/pR, and 93.7% of the expressed lipase activity was found in the culture medium upon heat induction, demon-strating the utility of the vector for expression and rapid extracellular assay of heterologous enzymes.